Perkembangan Green Banking Di Indonesia Berdasarkan Systematic Literature Review Periode 2019-2026 - Tri Hanani; Novia Rizki; Wulandari Agustiningsih (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2026)
This study aims to analyze the progress of research on green banking in Indonesia. This research uses a systematic literature review (SLR) method, conducting an in-depth review of previous studies. This study employs a Systematic Literature Review (SLR) of publications on green banking in Indonesia, following the PRISMA method. This study limits the research to the keywords "green banking" and "Indonesia" and to publication years from 2019 to 2026, as of June. The highest research trend was in 2024, and the lowest was in 2019, when quantitative methods were dominant. The outline of green banking research for the 2019-2026 period includes the influence of green banking on sustainability, the implementation of the green banking concept, the factors that influence or encourage its implementation in Indonesia, and the impact of green banking on company performance and efficiency